2014
DOI: 10.1002/bdrb.21104
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Effects and Reversibility of the Injuries Caused by Nandrolone Decanoate in Uterine Tissue and Fertility of Rats

Abstract: This study is the first to investigate the effects of different doses of nandrolone decanoate (ND) upon uterine tissue and fertility, and if the reproductive alterations can be restored after cessation of the treatment. Wistar female rats were treated with ND at doses of 1.87, 3.75, 7.5, and 15 mg/kg body weight, diluted in vehicle (n = 30/group), or received only mineral oil (control group, n = 45). The animals were divided into three periods of study: ND-treated receiving a daily subcutaneous injection for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…In this study, the final body weight of animals was not influenced by the treatments. Previous studies have shown no effect of synthetic steroids on the final body weight of rats, corroborating with our results . Mostafavi et al identified that melatonin as an adjunctive treatment has a buffering role on the side effects of several drugs on body weight.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the final body weight of animals was not influenced by the treatments. Previous studies have shown no effect of synthetic steroids on the final body weight of rats, corroborating with our results . Mostafavi et al identified that melatonin as an adjunctive treatment has a buffering role on the side effects of several drugs on body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with different doses of ND is capable of promoting oestrous acyclicity . In this study, the persistence of the dioestrus stage occurred even in androgenized groups that were treated with MLT.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, a previous study conducted in our laboratory (Belardin et al . ) showed that 60 days after last ND dose, the females were receptive to males as sperm was observed in vaginal smears, except to those females receiving the highest dose of ND (15 mg/kg). Only two females receiving 1.87 mg ND/kg became pregnant, and the rats receiving doses of 3.75 and 7.5 mg ND/kg probably did not ovulate because no uterine implantation and/or resorption site was found.…”
Section: Discussionmentioning
confidence: 98%
“…; Belardin et al . ). However, no study has evaluated the dose‐dependent effect of the ND on ovarian tissue and whether this effect can be reversed after discontinuing steroid treatment.…”
mentioning
confidence: 97%
“…However, the misuse of these substances has increase among women (Elliot and Goldberg 2000). Therefore, because there is evidence that AAS alters the female reproductive physiology (Belardin et al 2014), other studies need to be conducted to elucidate the changes induced by AAS in females, particularly the changes associated with the cardiovascular system and its regulation.…”
Section: Introductionmentioning
confidence: 99%